Convenient synthesis of arylboronates through a synergistic Pd/Cu-catalyzed miyaura borylation reaction under atmospheric conditions - Jadsada Ratniyom (2018)
A highly efficient and practical borylation reaction of aryl iodides with bis(pinacolato)diboron has been established. By using Pd(OAc)2, CuI, and PPh3as a ligand at room temperature under air in the presence of Cs2CO3, the protocol proved to be general. Various functionalized arylboronates were obtained in moderate to excellent yields. In addition, a possible reaction mechanism was proposed. An efficient borylation reaction of aryl iodides with bis(pinacolato)diboron is developed by using Pd(OAc)2and CuI. This catalytic system has high catalytic efficiency at room temperature in air and functional-group tolerance for a wide range of substrates. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.